第52次日本南極地域観測隊越冬報告2011-2012 - 宮本, 仁美; ミヤモト, ヒトミ; 堤, 雅基; ツツミ, マサキ; Miyamoto, Hitomi; Tsutsumi, Masaki (2014)
P(論文) 第52次日本南極地域観測隊越冬隊は，第Ⅷ期6か年計画の初年度を担う隊として，2011年2月1日に第51次日本南極地域観測隊越冬隊から昭和基地の運営を引き継いだ. 越冬期間中は，2011年2-5月，2011年12月及び2012年1月の月最深積雪の記録を更新し，2011年6-11月については観測史上第2位を記録するなど，一年を通じて積雪量がきわめて多く経過した. 重点研究観測として「南極域中層・超高層大気を通して探る地球環境変動」に基づき，南極大気の総合観測を開始した. ドロンイングモードランド航空網（DROMLAN）関連では昭和基地沖の海氷上に滑走路を造成し，乗員・乗客への気象情報や燃料の提供のほか，宿泊や食事の提供を行った. テレビ会議システムを用いた児童・生徒対象の「南極教室」を19回実施したほか，12回にわたり各種のイベントに出演した. 第53次行動において「しらせ」が18年ぶりに昭和基地沖に接岸できなかったことに伴い，2012年1月24日夜から2月10日朝にかけて，片道30kmに及ぶ氷上輸送を実施した. The outline of the activities of the 52nd Japanese Antarctic Research Expedition (JARE-52) wintering party is reported. JARE-52 wintering party conducted the first year research and logistical program in the eighth six-year plan of Japanese Antarctic Program after taking over management of Syowa Station from JARE-51 wintering party on February 1, 2011. Extremely deep snow was observed throughout the year. JARE-52 started the comprehensive observation of Antarctic atmosphere as one of the prioritized studies of the eighth six-year plan “The study of global climate change through the observation of the middle and upper atmosphere over the Antarctic”. JARE-52 developed runways on sea ice off the coast of Syowa Station for the Dronning Maud Land Air Network (DROMLAN). As outreach activities, remote class programs for children and students were performed 19 times through the satellite TV conference system from Syowa Station. Because the icebreaker Shirase could not reach the coast of Syowa Station for the first time in 18 years, long-distance transportation on sea ice was carried out from January 24 to February 10, 2012. departmental bulletin paper